Antibodies conjugated with viral antigens elicit a cytotoxic T cell response against primary CLL ex vivo - Schneidt, Viktor; Dreger, Peter; Zyl, Dwain George van; Delecluse, Susanne; Delecluse, Henri-Jacques (Leukemia, 2019)
Chronic lymphocytic leukemia (CLL) is the most frequent B cell malignancy in Caucasian adults. The therapeutic armamentarium against this incurable disease has recently seen a tremendous expansion with the introduction of specific pathway inhibitors and innovative immunotherapy. However, none of these approaches is curative and devoid of side effects. We have used B-cell-specific antibodies conjugated with antigens (AgAbs) of the Epstein-Barr virus (EBV) to efficiently expand memory CD4+ cytotoxic T lymphocytes (CTLs) that recognized viral epitopes in 12 treatment-naive patients with CLL. The AgAbs carried fragments from the EBNA3C EBV protein that is recognized by the large majority of the population. All CLL cells pulsed with EBNA3C-AgAbs elicited EBV-specific T cell responses, although the intensity varied across the patient collective. Interestingly, a large proportion of the EBV-specific CD4+ T cells expressed granzyme B (GrB), perforin, and CD107a, and killed CLL cells loaded with EBV antigens with high efficiency in the large majority of patients. The encouraging results from this preclinical ex vivo study suggest that AgAbs have the potential to redirect immune responses toward CLL cells in a high percentage of patients in vivo and warrant the inception of clinical trials.
Published online: 20 June 2018
Gesehen am 08.04.2019